Di Rancang Bangun Sistem Keamanan Terhadap Kunci Ruangan Berbasis Bot Telegram Menggunakan Mikrokontroler Esp8266: Rancang Bangun Sistem Keamanan Terhadap Kunci Ruangan Berbasis Bot Telegram Menggunakan Mikrokontroler Esp8266 - Timbo Faritcan Siallagan; Tita Tita (Journal of Information Technology, 2020)
ABSTRACTION A building or a house is a shelter and gathering of a family or group of people. One of the requirements for a safe house or building is a good door lock security system. Conventional doors use locks as a lock. This method has many security risks in terms of reliability and use. Among its weaknesses is that access to open or close keys can only be done by key holders and directly on the spot. Thus it will be difficult if you do security control of the door remotely, there is a risk of delay in handling the crime of theft, therefore an appropriate technology is needed to overcome this problem, namely a security system for the room where this system can be made based on Telegram Bot which uses a microcontroller. With the creation of such a system, the tools needed are microcontroller ESP8266 model, notepad ++ editors and Bascom AVR, using assembler programming language.